Establishment of a Pre-vascularized 3D Lung Cancer Model in Fibrin Gel—Influence of Hypoxia and Cancer-Specific Therapeutics - Kniebs, Caroline; Luengen, Anja Elisabeth; Guenther, Daniel; Cornelissen, Christian Gabriel; Schmitz-Rode, Thomas; Jockenhoevel, Stefan; Thiebes, Anja Lena (Frontiers in Bioengineering and Biotechnology, 2021)
Lung cancer is the most frequently diagnosed cancer worldwide and the one that causes the highest mortality. In order to understand the disease and to develop new treatments, in vitro human lung cancer model systems which imitate the physiological conditions is of high significance. In this study, a human 3D lung cancer model was established that features the organization of a tumor with focus on tumor angiogenesis. Vascular networks were formed by co-culture of human umbilical vein endothelial cells (HUVEC) and adipose tissue-derived mesenchymal stem cells (ASC) for 14 days in fibrin. A part of the pre-vascularized fibrin gel was replaced by fibrin gel containing lung cancer cells (A549) to form tri-cultures. This 3D cancer model system was cultured under different culture conditions and its behaviour after treatment with different concentrations of tumor-specific therapeutics was evaluated. The evaluation was performed by measurement of metabolic activity, viability, quantification of two-photon laser scanning microscopy (TPLSM) and measurement of the proangiogenic factor VEGF in the supernatant. Hypoxic conditions promoted vascularization compared to normoxic cultured controls in co- and tri-cultures as shown by significantly increased vascular structures, longer structures with a higher area and volume, and secretion of vascular endothelial growth factor. Cancer cells also promoted vascularization. Treatment with 50 µM gefitinib or 50 nM paclitaxel decreased the vascularization significantly. VEGF secretion was only reduced after treatment with gefitinib, while in contrast secretion remained constant during medication with paclitaxel. The findings suggest that the herein described 3D lung cancer model provides a novel platform to investigate the angiogenic potential of cancer cells and its responses to therapeutics. Thus, it can serve as a promising approach for the development and patient-specific pre-selection of anticancer treatment.